2023
DOI: 10.1177/09567976231194221
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Practices May Buffer the Impact of Adversity on Epigenetic Age Acceleration Among Young Children With Developmental Delays

Alexandra D. W. Sullivan,
Anne K. Bozack,
Andres Cardenas
et al.

Abstract: This study examined whether children exposed to adversity would exhibit lower epigenetic age acceleration in the context of improved parenting. Children with developmental delays and externalizing behavior problems ( N = 62; Mage = 36.26 months; 70.97% boys, 29.03% girls; 71% Latinx, 22.6% Black) were drawn from a larger randomized controlled trial (RCT), which randomized them to receive Internet-delivered parent–child interaction therapy (iPCIT; n = 30) or community referrals as usual (RAU; n = 32). Epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…In conclusion, the observed reduction in the DNAm-derived pace of aging and CRP, coupled with the absence of associations with IL-6 and PedBE age acceleration, 21 underscores the intricate association of parenting interventions with biological markers of aging and inflammation. The specificity of iPCIT intervention effects underscores the necessity of targeted interventions tailored to address distinct aspects of the complex biological and behavioral landscape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In conclusion, the observed reduction in the DNAm-derived pace of aging and CRP, coupled with the absence of associations with IL-6 and PedBE age acceleration, 21 underscores the intricate association of parenting interventions with biological markers of aging and inflammation. The specificity of iPCIT intervention effects underscores the necessity of targeted interventions tailored to address distinct aspects of the complex biological and behavioral landscape.…”
Section: Discussionmentioning
confidence: 99%
“… 18 One mechanism through which this phenomenon may occur is DNA methylation (DNAm), an epigenetic mark that can affect DNA transcription without changing the underlying sequence. 19 Supporting the idea that changes in DNAm are a mechanism for health disparities in children with developmental delay, research has demonstrated this epigenetic marker to be sensitive to the environment, including parenting 20 , 21 and stress, 22 especially during early childhood. 23 Because DNAm is critical for establishing and maintaining cell type identity, 19 differences in cell type proportions can also be informative of inflammation and health in oral tissues, 24 , 25 , 26 , 27 , 28 which may be particularly pertinent for those with developmental delays prone to oral bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, considering the small effect sizes observed, future research should explore moderating factors that could amplify or mitigate the association between child maltreatment and epigenetic aging. 58,59 Table 3…”
Section: Limitationsmentioning
confidence: 99%